2018
DOI: 10.1186/s13018-018-0871-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of glucosamine and chondroitin for the treatment of osteoarthritis: a meta-analysis of randomized controlled trials

Abstract: ObjectiveTo assess the symptomatic effectiveness and safety of oral symptomatic slow-acting drugs (SYSADOAs) on the treatment of knee and/or hip osteoarthritis, such as chondroitin, glucosamine, and combination treatment with chondroitin plus glucosamine.MethodsWe searched electronic database including PubMed, Embase, Cochrane Library, and the reference lists of relevant articles published from inception to May 22, 2018. An updated meta-analysis was performed to assess the effectiveness of these slow-acting dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
28

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 42 publications
4
79
1
28
Order By: Relevance
“…These results are in line with those observed with large doses of some well-studied cartilage-protecting agents, such as glucosamine and chondroitin, both exerting a certain degree of anti-inflammatory and anti-pain effect in OA patients [46].…”
Section: Discussionsupporting
confidence: 89%
“…These results are in line with those observed with large doses of some well-studied cartilage-protecting agents, such as glucosamine and chondroitin, both exerting a certain degree of anti-inflammatory and anti-pain effect in OA patients [46].…”
Section: Discussionsupporting
confidence: 89%
“…The most recent literature suggests that chondroitin sulfate, alone or associated with glucosamine (CS), is an effective treatment for osteoarthritis, according to most of the available studies published in the period 2008–2018. 1 8 Although doubts were raised in a meta-analysis published in 2010, 9 the reliability of the results of this study was highly questioned due to possible methodological deficiencies. 10 12 On the other hand, the efficacy of CS has been confirmed more recently in three randomised, double-blind clinical trials in patients with knee osteoarthritis: the MOVES 4 study, in which it was found that the combination of CS with glucosamine would have similar efficacy to that of celecoxib; in the MOSAIC 5 study, in which the superiority of CS over celecoxib in reducing cartilage volume loss was demonstrated through a 2-year follow-up; and finally, in the CONCEPT 6 study, in which CS was superior to placebo and similar to celecoxib in reducing pain and improving joint function for 6 months in symptomatic patients.…”
Section: Introductionmentioning
confidence: 83%
“…These results were also confirmed in a meta-analysis published in 2018. 8 CS is currently recommended for the treatment of knee osteoarthritis by, among others, the guidelines of the Spanish Society of Rheumatology, 13 , 14 the European League Against Rheumatism 15 and those published by the European Society for Clinical and Economic Aspects of Osteoporosis, Osteoarthritis and Musculoskeletal Diseases (ESCEO). 16 …”
Section: Introductionmentioning
confidence: 99%
“…Although these trials each varied somewhat in terms of outcomes, each showed an effect from either glucosamine or chondroitin on pain and/or function. [38][39][40] Of the two metaanalyses that looked at the combination of glucosamine plus chondroitin, no significant benefit was demonstrated for the two together. An additional 2019 meta-analyses specifically looked at safety (rather than efficacy), and demonstrated that both glucosamine and chondroitin are considered safe, with neither being associated with increased adverse events compared with placebo.…”
Section: Nutritional Supplementsmentioning
confidence: 99%